European ancient settlements – A guide to their composition and morphology based on soil micromorphology and associated geoarchaeological techniques; introducing the contrasting sites of Chalcolithic Borduşani-Popină, Borcea River, Romania and Viking Age Heimdaljordet, Vestfold, Norway. (1st December 2017) - Macphail, Richard I.; Bill, Jan; Crowther, John; Haită, Constantin; Linderholm, Johan; Popovici, Dragomir; Rødsrud, Christian Løchsen
Abstract: Specific soil micromorphological, broader geoarchaeological and environmental archaeology signatures of settlement activities and land use have been identified from numerous case studies across Europe – from Romania to western Norway. In order to demonstrate how such investigations contribute to our understanding of settlement morphology and its wider landscape, an improved way of organising site-specific information or guide was created (Macphail and Goldberg, in press). Activities and land use are divided into 'Within Settlement', 'Peripheral to Settlement' and 'The Settlement's Wider Landscape'. Major themes identified are: Constructions (and materials), Trackways and paths (and other communication/transport-associated features), Animal Management, Water Management, Waste Disposal (1: middening; 2: human waste), Specialist Domestic and Industrial Activities and Funerary Practices. In the case of trackway deposits, their characterisation aids the identification of intensely occupied areas compared to rural communications, although changing land use within urban areas has also produced 'rural signatures' (e.g. as associated with animal management), for example in Late Roman cities. Specialist activities such as fish and crop processing or working with lead and other metals, in-field and within-wall manuring, stabling and domestic occupation floor-use evidence, and identification of different funerary practice – cremations, boat graves and other inhumations, and excarnation features – and peripheral constructions such as boat-houses, are also noted. New information from the Chalcolithic tell site of Borduşani-Popină, Romania and seasonally occupied Viking settlement of Heimdaljordet, Norway, is introduced.